Mulheres gestantes em situação de rua: um estudo na perspectiva feminista - Arévalo, Roseane Ribeiro (2023)
The research presented, aims to make a study of pregnant women living on the streets from a feminist perspective. We start from the understanding that feminism has an important contribution within the historical context of society, in which they present struggles that were won when women took to the streets to claim our rights. Within this context, it was observed that the agenda of pregnant women living on the streets is still far from feminist collectives, it was important to make this observation through field research that was giving a north for this problematization to be debated. Bibliographical readings on the gender debate, researchers who have been discussing the topic, were necessary for this work to be carried out. I tried to point out the lack of public policies of the State, which is quite silent with regard to assistance and financial investment for women living on the streets. We observe that, unfortunately, violence against women is present in different parts of society and at the same time forms of resistance are being created in the face of this violence. These women's right to motherhood must be guaranteed, the removal of their baby is not a form of protection, it is inhumane and reinforces patriarchal, sexist, racist and capitalist actions. Feminism can and must, together with other groups that work in the defense of human rights, guide this demand, whether by participating in public policy conferences for women, health, social assistance or also finding ways to approach them, listening to their stories. of life